PEMBINAAN KEMANDIRIAN DALAM MENINGKATKAN KETERAMPILAN KEWIRAUSAHAAN BAGI NARAPIDANA PADA LAPAS KLAS IIA MATARAM - Nabil Naufal; Mitro Subroto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
in the criminal justice system in Indonesia there are 4 subsystems consisting of the police, prosecutors, courts and correctional institutions. Convicts are the designation for convicts who are serving a crime of losing their independence in Correctional Institutions. channel their interests, talents and expertise and skills while they are serving their sentence, the independence coaching program is carried out using a skills training approach and independent activities for convicts so that the hope is that after they have finished serving their sentence in prison and leave, they will return to society. skills that can be used as a source of income, this type of research is descriptive qualitative with the research location at the Mataram Class IIA Correctional Institution, the results of this study indicate that the implementation of the coaching program The inmates at the Mataram class IIA penitentiary are going quite well. The suggestion from this research is that it is necessary to pay more attention to the cooperation between prisons and the government regarding coaching. In addition, it is necessary to observe the correctional center or social counselor to find out whether the skills training provided in prisons is beneficial and sustainable